2018
DOI: 10.1182/bloodadvances.2017013672
|View full text |Cite|
|
Sign up to set email alerts
|

2-O, 3-O desulfated heparin mitigates murine chemotherapy- and radiation-induced thrombocytopenia

Abstract: Key Points• ODSH counters the inhibitory effect of PF4 on megakaryopoiesis in murine and human cell cultures.• ODSH improves platelet count recovery in murine models of both CIT and RIT.Thrombocytopenia is a significant complication of chemotherapy and radiation therapy.Platelet factor 4 (PF4; CXCL4) is a negative paracrine of megakaryopoiesis. We have shown that PF4 levels are inversely related to steady-state platelet counts, and to the duration and severity of chemotherapy-and radiation-induced thrombocytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Thrombocytopenia caused by long-term radiotherapy and chemotherapy exists in cancer treatment ( Tkaczynski et al, 2018 ; Kiang et al, 2014 ). This complication seriously affects the prognosis and endangers the life of patients ( Mouthon et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombocytopenia caused by long-term radiotherapy and chemotherapy exists in cancer treatment ( Tkaczynski et al, 2018 ; Kiang et al, 2014 ). This complication seriously affects the prognosis and endangers the life of patients ( Mouthon et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, radiotherapy and chemotherapy for tumor treatment are the key factors leading to thrombocytopenia complications. Radiation-induced thrombocytopenia (RIT) is a significant cause of morbidity and mortality and is particularly important in the hematopoietic form of acute radiation syndrome ( Tkaczynski et al, 2018 ). According to several studies, platelet count correlates more strongly with survival following total body irradiation than any other hematologic parameter ( Mouthon et al, 1999 ; Kiang et al, 2014 ; Lebois et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia is a primary complication of radiotherapy that can be life threatening. Platelet count was reported to be an important indicator of surviving radiation exposure [ 36 , 37 ]. However, the clinical treatment of thrombocytopenia is usually insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The derivative was well tolerated and the combination was associated with a high rate (92%) of morphologic complete remissions. The rapid hematological recovery was also encouraging, an effect that could be related to the binding and neutralization of platelet factor 4, a negative regulator of megakariopoiesis [ 195 ]. Interestingly, parallel in vitro studies suggested that CX-01 may interfere with the CXCL12/C–X–C chemokine receptor 4 (CXCR4) axis implicated in the homing of leukemic stem cells in marrow stromal niches via competitive inhibition for the binding of CXCL12 to the marrow HS [ 186 ].…”
Section: Non-anticoagulant Heparin Derivatives and Oligosaccharidimentioning
confidence: 99%